Factors Affecting the Use of Islamic E-Wallets in Indonesia: A Technological Perspective - Dikdik Saleh Sadikin; Raden Bambang Budhijana (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
The study aimed to examine the causal relationship among those variables, entitled the factors influence on e-wallet Islamic platform in Indonesia. The object of the study was customers of e-wallet digital payment with the target respondents who were in the territory of Indonesia. The data collection method in this study used an online survey or questionnaire with the SmartPLS 3.0 application tool.  Analysis of the effects on the e-Wallet Digital Finance uses a Structural Equation Model (SEM) with Partial Least Square (PLS) approach. PLS is a components or variants-based structural equation model. PLS is a powerful method analysis because it is not based on assumptions, so the data does not have to follow standard distribution, and the sample size also doesn’t have to be large. The research results can be illustrated that Islamic e-wallets can be optimized through the Customer-Based Corporate Reputation Dimension; Perceived Risk; Perceived Value, and the Customer Product Adoption Proneness. From the Islamic e-wallet research result shows that Perceived Risk has no effect on Perceived Value and Perceived Risk becomes lower when the Customer-Based Corporate Reputation Dimension is well improved. These results can be advantaged for Islamic e-wallet to be introduced and recommended to wider society as the save e-wallet with lower risk.